A Golden Formula in Neoclassical‐Growth Models with Brownian‐Motion Shocks. (6th March 2014) - Dai, Darong
Abstract In the paper, a Golden Formula, which does not depend on the specification of production and preference functions, is established to reveal that time‐average of the growth rate of optimal capital accumulation will converge to a constant, which is endogenously determined by relevant parameters, almost surely. The Golden Formula naturally implies surprisingly interesting and also intrinsic economic relations between some important macroeconomic variables; for example, it serves as a direct bridge between the modified Golden Rule and the modified Ramsey Rule. Furthermore, it indeed subsumes and hence substantially extends the classical Golden Rule in deterministic theory.